An exceptional finding in an explanted liver: a case report of cirrhotomimetic hepatocellular carcinoma - Aby, Elizabeth S.; Lou, Susan M.; Amin, Khalid; Leventhal, Thomas M. (Frontiers in Gastroenterology, 2023)
We present a case of cirrhotomimetic hepatocellular carcinoma (HCC) diagnosed on explant following liver transplantation (LT). Pre-LT computerized tomography scan demonstrated a nodular, cirrhotic appearing liver; there was no evidence of lesions consistent with HCC. Serum alpha-fetoprotein one month pre-LT was 4 ng/dL, which was within normal limits. Following LT, the patient underwent surveillance for HCC. Eight months post-LT, he was noted to have lytic osseous lesions in his sternum and T10 vertebral body. Biopsies of these lesions demonstrated metastatic poorly differentiated carcinoma, concerning for metastatic HCC. It is important to spread awareness about cirrhotomimetic HCC as it often evades current screening and if patients are inadvertently transplanted with cirrhotomimetic HCC, this can have significant downstream consequences. A multidisciplinary team approach is critical to ensure early detection of any recurrence and timely treatment.